Potentially Inappropriate Medication Prescribing in Older Adults According to EU(7)-Potentially Inappropriate Medication List: A Nationwide Study in Portugal - Daniela A. Rodrigues, MSc; Ana I. Plácido, PhD; Ana Bárbara Tavares, PharmD; Daniela Azevedo, MSc; Ramona Mateos-Campos, PharmD, PhD; Adolfo Figueiras, PharmD, PhD; Maria Teresa Herdeiro, PharmD, PhD; Fátima Roque, PharmD, PhD (Elsevier, 2022)
ABSTRACT: Background: Portugal has among the highest rates of dependency among older adults in Europe. Older adults with aging-related comorbidities are prone to the use of potentially inappropriate medication (PIM). Objective: The aim of this study was to analyze PIM prescriptions in older Portuguese adults, as well as the change rate of PIM prescriptions over time, and assess the geographical variability between the different regions of mainland Portugal. Methods: Using a national database, PIM prescriptions were analyzed for older adults (aged 65 years and older) between 2019 and 2021 from 2 perspectives: PIM-defined daily dose (DDD) frequency (%) and DDD per 1000 inhabitants per day (DID). Results: Overall, mainland Portugal presented a PIM DDD frequency of 9.20%, which was relatively higher in Alentejo and Centro and lower in the North. Alprazolam, fluoxetine, and rivaroxaban were PIM with higher DDD frequency values. Over the years, the DID change rates for these three PIM were -3.80%, -14.86%, and +18.54%, respectively, depending on the geographic region. Alprazolam and fluoxetine were mostly prescribed to older women, whereas rivaroxaban was mostly prescribed to older men. Conclusions: These results emphasize the need to implement initiatives and interventions to decrease PIM prescriptions in older adults.